(untitled) (Orfeu, 2025)
Analysis of the colour sequence of Ivan the Terrible, Part 2, by Sergei Eisenstein, with music by Sergei Prokofiev, showing the importance of experimentation in the composition process – both of the scene and of the music. Free experimentation occurs mainly in the use of interchangeable modules, written by Prokofiev and used freely in the montage.